PEMANFAATAN MEDIA MONOPOLI UNTUK MENINGKATKAN KEAKTIFAN DAN HASIL BELAJAR IPA SISWA KELAS III SDN SUGIHWARAS KECAMATAN MAOSPATI KABUPATEN MAGETAN TAHUN PELAJARAN 2015/2016 - Anang Gatot Subroto; R. Bekti Kiswardianta; M.S Djoko Laksana (Florea : Jurnal Biologi dan Pembelajarannya, 2016)
Education is an important role in improving human resources. SDN Sugihwaras 2 Maospati have adequate facilities and infrastructure, but its use is not maximized. Such conditions make the learning  in the classroom in which there are still many students spoke with fear, students tend to give silent resulted in low learning outcomes. Implementation of education are encouraged to use effective learning media that give pleasure to support student learning outcomes give liveliness. Based on these problems, researchers conduct studies in SDN Sugihwaras 2 Maospati. Media monopoly in learning aims to enhance the activity and learning outcomes third grade students in sci ence subjects. The research was conducted in the SDN Sugihwaras 2 Maospati. Data collection techniques were used that observation, documentation, tests, and interviews. Results showed that the average use of  monopoly can enhance the activity of learning outcomes. Data were obtained that the learning outcomes of the first cycle completeness 45% give students who are not on 55% due to the secondcycle increased to 75% Students who complete 25% give students conclusion is not. Liveliness to the  results of the first cycle 20% liveliness students are active, 45% of students are quite active, give 35% of students are less active. In the second cycle there is an increasing involvement of the student to be 70% of active students. It can be concluded there is an increase learning outcomes and student activity by monopoly media.